Programmable rainbow-colored optofluidic fiber laser encoded with topologically structured chiral droplets - Wang, Chenlu (2022)
Optofluidic lasers are emerging building blocks with immense potential in the development of miniaturized light sources, integrated photonics, and sensors. The capability of on-demand lasing output with programmable and continuous wavelength tunability over a broad spectral range enables key functionalities in wavelength-division multiplexing and manipulation of light-matter interactions. However, the ability to control multicolor lasing characteristics within a small mode volume with high reconfigurability remains challenging. The color gamut is also restricted by the number of dyes and emission wavelength of existing materials. In this study, we introduce a fully programmable multicolor laser by encapsulating organic-dye-doped cholesteric liquid crystal microdroplet lasers in an optofluidic fiber. A mechanism for tuning laser emission wavelengths was proposed by manipulating the topologically induced nanoshell structures in microdroplets with different chiral dopant concentrations. Precision control of distinctive lasing wavelengths and colors covering the entire visible spectra was achieved, including monochromatic lasing, dual-color lasing, tri-color lasing, and white colored lasing with tunable color temperatures. Our findings revealed a CIE color map with 145% more perceptible colors than the standard RGB space, shedding light on the development of programmable lasers, multiplexed encoding, and biomedical detection.